Linking power Doppler ultrasound to the presence of th17 cells in the rheumatoid arthritis joint. - Nicola J Gullick; Hayley G Evans; Leigh D Church; David M Jayaraj; Andrew Filer; Bruce W Kirkham; Leonie S Taams (PLoS ONE)
Background Power Doppler ultrasound (PDUS) is increasingly used to assess synovitis in Rheumatoid Arthritis (RA). Prior studies have shown correlations between PDUS scores and vessel counts, but relationships with T cell immunopathology have not been described. Methodology/principal findings PBMC were isolated from healthy controls (HC) or RA patients and stimulated ex vivo with PMA and ionomycin for 3 hours in the presence of Golgistop. Paired synovial fluid (SF) or synovial tissue (ST) were analysed where available. Intracellular expression of IL-17, IFNgamma, and TNFalpha by CD4+ T cells was determined by flow cytometry. Synovial blood flow was evaluated by PDUS signal at the knees, wrists and metacarpophalangeal joints of RA patients. Serum, SF and fibroblast culture supernatant levels of vascular endothelial growth factor-A (VEGF-A) were measured by ELISA. The frequency of IL17+IFNgamma-CD4+ T cells (Th17 cells) was significantly elevated in peripheral blood (PB) from RA patients vs. HC (median (IQR) 0.5 (0.28-1.59)% vs. 0.32 (0.21-0.54)%, p = 0.005). Th17 cells were further enriched (mean 6.6-fold increase) in RA SF relative to RA PB. Patients with active disease had a higher percentage of IL-17+ T cells in ST than patients in remission, suggesting a possible role for Th17 cells in active synovitis in RA. Indeed, the percentage of Th17 cells, but not Th1, in SF positively correlated with CRP (r = 0.51, p = 0.04) and local PDUS-defined synovitis (r = 0.61, p = 0.002). Furthermore, patients with high levels of IL-17+CD4+ T cells in SF had increased levels of the angiogenic factor VEGF-A in SF. Finally, IL-17, but not IFNgamma, increased VEGF-A production by RA synovial fibroblasts in vitro. Conclusions/significance Our data demonstrate a link between the presence of pro-inflammatory Th17 cells in SF and local PDUS scores, and offer a novel immunological explanation for the observation that rapid joint damage progression occurs in patients with persistent positive PDUS signal.